(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The article will consider how, based on the sci-fi novel “Roadside Picnic” (1972) by Arkady and Boris Strugatsky, director Andrei Tarkovsky shot the author’s film “Stalker” (1979). film adaptation of a literary work, that is, he translated the novel from the language of literature into the language of the film and transferred it from the sci-fi genre to the non-genre art film. It also deals with the filmography of Andrei Tarkovsky and his screenwriters, about the work on writing the script for the film “Stalker” and the problems associated with creating of the script. According to the idea of Andrei Tarkovsky, ​​the director of the film “Stalker”, a radical adaptation of the novel “Roadside Picnic” by A. and B. Strugatsky was made, which has little in common with original literary piece. Keywords: Andrey Tarkovsky, Strugatsky brothers, science fiction, literature and film, film adaptation, art film.